2016
DOI: 10.1136/annrheumdis-2016-eular.1954
|View full text |Cite
|
Sign up to set email alerts
|

OP0224 Filgotinib (GLPG0634), An Oral Jak1 Selective Inhibitor Is Effective in Combination with Methotrexate in Patients with Active Rheumatoid Arthritis: Results from A 24-Week Phase 2B Dose Ranging Study: Table 1.

Abstract: BackgroundFilgotinib (GLPG0634) is a novel oral selective JAK1 inhibitor that was evaluated in a 24-week phase 2B study in combination with methotrexate (MTX) in active rheumatoid arthritis (RA) with inadequate response to MTX. The primary endpoint of proportion of patients achieving ACR20 response after 12 weeks of treatment was met.ObjectivesTo present the results of the 24-week analysis.MethodsPatients with active RA on stable dose of MTX were randomized 1:1:1:1:1:1:1 in a double blinded manner to receive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Additionally, ACR20 response rates of this approximate magnitude have been seen in other contemporary clinical trials 425 29–31 Thus, the placebo ACR20 response observed in the RA-BUILD trial appears to be within contemporary norms and was not driven by geographic outliers.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, ACR20 response rates of this approximate magnitude have been seen in other contemporary clinical trials 425 29–31 Thus, the placebo ACR20 response observed in the RA-BUILD trial appears to be within contemporary norms and was not driven by geographic outliers.…”
Section: Discussionsupporting
confidence: 55%
“…The observed placebo response in BALANCE II was higher than previously reported for RA trials conducted several years prior to this study. In the placebo group, 46% of patients achieved an ACR20 response at week 12, with a clear regional variance in response contributing to this effect, which may reflect the tendency toward increasing placebo responses as demonstrated by contemporaneous clinical trials in this group (see Supplementary Table 1, http://onlinelibrary.wiley.com/doi/10.1002/art.39808/abstract). Regional differences in patients’ expectations and perceptions of treatment efficacy may contribute to the trend recently observed in RA clinical trials and may reflect patients’ attitudes toward more advanced treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Filgotinib is one such inhibitor, which blocks JAK1 with 30‐fold selectivity over JAK2 . It has been effective in multiple phase II trials in RA, showing efficacy as monotherapy, in combination with MTX, and in patients with an inadequate response to MTX . There are 20 ongoing clinical trials with filgotinib underway in a wide range of autoimmune diseases, including phase 3 trials (Table ; Fig.…”
Section: Next‐generation Selective Jakinibsmentioning
confidence: 99%